Tuning the gel size and LCST of N-isopropylacrylamide nanogels by anionic fluoroprobe - Koc, Kenan; Alveroglu, Esra (SPRINGER, 2016)
Varying size fluorescent N-isopropylacrylamide (NIPAM) nanogels were synthesized from 140 to 550 nm by precipitation copolymerization. N,N-methylenebisacrylamide (BIS) and ammonium persulfate APS were used as cross-linker and initiator, respectively. 8-Hydroxypyrene-1,3,6-trisulfonic Acid (Pyranine, Py) molecules were used for controlling the particle size and lower critical solution temperature (LCST) of nanogels. NIPAM, BIS and APS amount were kept constant and Py amount changed to tailor the particle size. Fluorescence spectroscopy, atomic force microscopy and light scattering methods show that Py caused smaller size nanogels due to the electrically charged side groups. Additionally, as seen from the light scattering experiment, LCST of nanogels is getting decrease considerably with increasing Py amount. Using of Py for tuning, the gel size and LCST were found very useful, easy and effective way, and it can be used for many biomedical applications.
Keywords: Nanogel; Pyranine; Poly(N-isopropylacrylamide); LCST; PRECIPITATION POLYMERIZATION; MICROSPHERES; TRANSITION; MICROGELS; HYDROGELS; BEHAVIOR; Chemistry; Polymer Science